Dari Buku ke Layar: Inovasi Media Digital dalam Merancang Bahan Ajar Sejarah yang Interaktif bagi Siswa Gen Z SMA Negeri 1 Tebing Tinggi - Nadya Anisa Iffa; Maulidya Dwi Melantika; Pahmi Kurniawan; Sani Safitri; Rani Oktapiani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
The 21st century of digitalization is very influential in life such as Education which must adapt to the development of world digitalization technology. Education is carried out by involving innovation, creativity, and also motivation to update more interesting learning methods with interactive media that have been designed. History learning in particular must develop and adapt to the digital era by utilizing technology to make teaching methods the goal of an active learning process. History learning which is considered boring has a great opportunity to be able to adapt to interactive media so that passive students during learning are reduced and become active students and can understand History easily. In this study involved a teacher with 30 high school students who were the objects of the research study. The method used was descriptive qualitative which refers to observation, documents, interviews, questionnaires, and also a social science approach. The results of the study explain the low interest in History learning to many passive students due to learning methods that are not in line with the digital era to attract Gen Z’s interest in History Lessons and also show the results of History learning by involving interactive media with digital technology.